High natural gamma radiation in two Brazilian areas - Bonotto, Daniel Marcos [UNESP] (My University, 2013)
Primeval radionuclides have survived in detectable amounts since the time of nucleosynthesis and contribute to the natural terrestrial radioactivity. The major contribution comes from 40K and radionuclides generated through the sequence of decay transformations of the three alpha emitting radionuclides: 232Th, 238U, and 235U. Each radioactive series ends by a stable Pb isotope after passing through several unstable members having half-lives much shorter than that of the respective precursors. Gamma rays of variable energy are emitted along these steps, constituting important records of the presence of natural radioactivity in soils and rocks. The South-east region of Brazil is known for its heavy mineral deposits like monazite, zircon, ilmenite, magnetite and pyrite that exhibit enriched concentrations for U, Th and rare earth elements (REE). These heavy mineral rich deposits are found as scattered bodies on different areas like in marine profiles or in the alkaline massif of PoÇos de Caldas, Minas Gerais State. Most of them are often associated with high 232Th levels, whereas others have high 238U and 40K concentrations too. Some of these heavy mineral deposits are from Quaternary and occur as sparse and discontinuous patches along the south-eastern coast of Brazil. Another important occurrence corresponds to Morro do Ferro that is situated near the center of the PoÇos de Caldas plateau and initially drew the attention of mining prospectors due to the abundant occurrence of magnetite veins and dykes. It is a small hill located near the intersection of a fractures system, rising some 140 meters above the plateau base level and lying five kilometers to the north of the Osamu Utsumi uranium mine and about 10 km to the south of the city of PoÇos de Caldas. The superficial radioactivity in this area was systematically investigated in the mid 60s with the aim of evaluating the effects of the accentuated radioactivity in the ore body environment. The level of the environmental gamma radiation close to the top of the hill varied between 1 and 3 mR/h (100-300 times higher than the background) in an area of about 30,000 m2 and the plants were so radioactive due to the 228Ra absorption that could generate autoradiographic images. The exposition of rodents to thoron decay products resulted in an average dose of 300 rem/year in epithelial cells of bronchi. This chapter reports the results of some investigations held in two Brazilian areas possessing high natural gamma radiation levels, with possible implications for human health. © 2013 by Nova Science Publishers, Inc. All rights reserved.